Density structure, flexure, and tectonics of the Iquique Ridge, northern Chile. (November 2021) - Contreras-Reyes, Eduardo; Obando-Orrego, Sebastián; Geersen, Jacob; Bello-González, Juan Pablo
Abstract: Kinematic paleo-reconstruction plate models show that the portion of the Iquique Ridge (IR) located next to the northern Chilean trench was formed 45–50 Ma onto the former oceanic Farallon (currently Nazca) plate near the intersection of the Foundation hotspot and the ancient Farallon-Pacific spreading center. The IR started to collide with South America >40 Ma off northern Peru, and the collision point started to migrate progressively southwards until present becoming northern Chile (20°-22°S) the current collision zone. In order to better understand the mechanical properties of the former oceanic Farallon plate during the IR formation, we used bathymetric and gravimetric data to characterize the hotspot swell and crustal structure of the IR. Results show an anomalous thick crust (10–15 km total thickness) that is capable of producing most of the swell topography (~200 km wide and 500–1000 m high) under nearly isostatic conditions (elastic thickness T e  < 5 km, which is consistent with a hotspot track formed onto young oceanic lithosphere < 5 Ma). The swell and anomalous thick crust of the IR is heterogeneously distributed suggesting discontinuous magmatic pulses from the Foundation hotspot to the overlying oceanic lithosphere. As the 45–50 Ma oceanic Nazca plate approaches to the northern Chilean trench, a well pronounced fore-bulge (>200 km wide and >500 m in amplitude) develops accompanied by tensional faulting related to plate bending. By simultaneously modelling, the shape of the outer rise and the hotspot swell topography adjacent to the IR in the ridge-trench collision zone, we find a decrease in T e towards the trench axis (10–50%). This trenchward T e reduction is interpreted in terms of plate weakening caused by fracturing and hydration of the oceanic lithosphere as its yield strength is exceeded by plate bending under conditions of high plate curvatures (>10 −7  m −1 ). Highlights: The Iquique Ridge overlies an anomalous thick crust that was formed under isostatic conditions ( T e < 5 km). The anomalous thick crust beneath the Iquique Ridge is heterogeneously distributed. We report a trenchward decrease in T e (10–50%) off northern Chile.